ENTERPRISE – UNIVERSITY FEDERATION AS DISTRIBUTED MEASUREMENT SYSTEM LABORATORY - Elenkov, Andrey Angelov (International Journal of Computing, 2014)
Federation allows a user to associate two accounts with each other. In this paper one account is the enterprise, the other one is the university. The student is the user which associates the two accounts. The goal is the student’s education from the university, for the enterprise’s needs, using enterprise’s infrastructure, especially enterprise distributed measurement system. A federation scenario for a distributed measurement system laboratory is discussed and a test system is built to test this scenario.